Qualitative Study: Strategies of Madrasah Principals in Managing School Environmental Health Post-COVID-19 Pandemic in Nganjuk - Toha Ma'sum (Pascasarjana Manajemen Pendidikan Islam STAI Darussalam Nganjuk, Indonesia, 2025)
This qualitative study investigates the strategies employed by Madrasah principals in managing school environmental health following the COVID-19 pandemic in Nganjuk, East Java. Through in-depth interviews with 15 principals and participatory observation across 10 rural Islamic schools (Madrasah Ibtidaiyah), the research identified critical approaches to sustaining hygiene and health protocols amid resource constraints. Thematic analysis revealed three core strategies: (1) Reinforcing Taharah (Cleanliness) as Religious Practice, where principals integrated handwashing and sanitation into wudu (ablution) routines, framing hygiene as an extension of Islamic purity obligations; (2) Adaptive Infrastructure Management, including repurposing zakat (alms) funds for touchless sinks and reorganizing prayer spaces to ensure physical distancing without disrupting religious activities; and (3) Community-Based Surveillance, leveraging parental networks (Majelis Taklim) for health monitoring and stigma reduction. Principals navigated challenges such as limited clean water access by collaborating with local pesantren (Islamic boarding schools) to share filtration systems, demonstrating resource-sharing rooted in Ukhuwah Islamiyah (Islamic solidarity). Findings underscore how principals blended religious values with practical innovation, transforming standard health protocols into culturally resonant actions. This alignment strengthened compliance—schools implementing Taharah-focused strategies reported 40% higher student hygiene adherence than those using generic protocols. The study argues that post-pandemic environmental health management in Islamic educational settings benefits from embedding secular requirements within religious frameworks, ensuring sustainability through community ownership. Recommendations include integrating fiqh al-bi‘ah (Islamic environmental jurisprudence) into principal training programs to bridge health policy and faith-based leadership.